Trade openness and the environmental Kuznets curve: Evidence from Chinese cities. (19th September 2018) - Fang, Zheng; Huang, Bihong; Yang, Zhuoxiang
Abstract: This paper examines the impact of economic growth and trade openness on environment in 261 Chinese cities over the period of 2004–2013, using recently developed continuously updated fully modified method which allows for both cross‐sectional dependence and endogeneity. Two types of pollutants, industrial waste water and sulphur dioxide are investigated, and three measures of openness are employed in the regression. From the results, we find that the environmental Kuznets curve hypothesis holds not only for the whole China, but also in different regions. It is estimated that wastewater pollution increases with economic development until per capita GDP reaching the turning point of 42, 991–48, 828 yuan (in constant 2002 price), which varies depending on the specific measure of trade openness. The turning point for sulphur dioxide is found to occur at a much lower income level around 9, 588–10, 663 yuan per capita GDP. Furthermore, export is mostly found to be positively related with pollution and the impact of import is likely to be negative for both the whole China and across regions, if the significance is identified in the estimation results.